TEACHERS’ STRATEGIES IN TEACHING SPEAKING AT SMP NEGERI 18 MEDAN - nisya anizar; beatrik nuyen saragih; tria wahyuni feronika sinaga (elt, 2019)
This research is aimed to find the teachers’ strategies in teaching English. This study was conducted to the eight grade students of SMP N 18 Medan. The research was conducted by using descriptive qualitative research design. The intruments used in this research were observation and interviewd. The researchers needed few days in collecting the data. From the data analysis, the researchers found that the strategies used by the teachers in teaching speaking were role play, drill and listen and repeat strategy.